Taxonomy, ecology and fishery of pen shells and some aspects of the reproductive biology of Atrina pectinata in the Northern Iloilo, Philippines - Jela, Cheryl B.
Pen shells are large bivalves taht are almost buried in soft substrates in shallow waters in the Philippines and globally. Their accessibility to local divers is a key factor to observe declining levels of their population. This study assessed the fishery and and ecology, investigated the morphological characteristics of pen shells in the Visayan sea,Philippines, and evaluates some aspects of the reproductive biology of Atrina pectinata. Surveys were conducted using self-structured questionnaires to pen shell collectors. Results showed that pen shell collectors were exposed to several problems. affecting their livelihood and well-being - such as low income due to frequently caught under-sized adductor muscles, unsafe to breathing apparatus underwater, and low level of education. In this study, pen shells were collected using compressor diving from pre-selected six stations located at different depths. Collected specimens were subjected to morphological and histological analyses. a total of 11 species were recorded during the wet and dry seasons. This represented an average of 63.64% increase from the previously recorded number of species in the area. The number of individuals was higher during the wet season (n=408) compared to dry season (n=93). A pectinata was almost abundant (58.1% of total) and occurred most abundant (58.1% of total) and occurred most frequently in the A. pectinata was most abundant (58.1% of total) and occurred most frequently in deeper area of station 6 (3.93±1.5 ind. ⁻¹ 100 m⁻² and least dominant in station 3 (1.47±1.04 ind.⁻¹ 100 m⁻²). A. pectinata in the northern Iloilo were observed to be dioecious with population skewed towards male (1.51:1) and number of male were observed to be significantly different from female (p=0.001). The fecundity ranged from 530,580 to 2,531,130 with an average of 1,283,119 SE±12103 eggs from specimens with shell length ranging from 196.02 to 313.71 mm. Two major spawning peaks occurred, one in August (30.7 ℃) and another peak in December (28.1℃) to February (29.8℃). There was no significant relationship between Gonadosomatic Index and temperature (r=0.03, p>0.05). In female, the length at which 50% of the population was mature was 186.29 mm and 149.82 mm for male. These are relevant information especially for policy formulation and management of pen shell resource.